Free drawing learning to recognize children’s characters - Farida Mayar; Febri Wandha Putra; Rima Pratiwi Fadli (International Journal of Evaluation and Research in Education (IJERE), 2022)
This descriptive qualitative study described the personality or characteristics of children based on the colors used in drawing activities. The subjects in this study were the Pembina Kindergarten students in the city of Padang, West Sumatra, Indonesia. They were determined by using snowball sampling technique. The data collected through observations and documentation analysis by researchers without being directly involved in activities. The data analysis technique used was an interactive model which consists of three activity lines: i) Data reduction; ii) Data display; and iii) Drawing conclusions and data verification.